Encoding motion events in Mandarin Chinese a cognitive functional study - Lin, Jingxia (Studies in Chinese language and discourse ;, 2019)
"This book is a corpus-based description and discussion of how Modern Mandarin Chinese encodes motion events, with a focus on how the distribution of verbal motion morphemes is closely associated to the meanings they lexicalize. The book is not only the first work that proposes a finer-grained classification and diagnostics of Chinese motion morphemes from the perspective of scale structure, but also the first to more comprehensively account for the ordering of Chinese motion morphemes. The findings of this study will not only enrich the literature on motion events, but more importantly, further our understanding of the nature of motion events and the way motion events are conceived and represented in the Chinese language. The major proposals and the scalar approach of this work will also shed light on studies beyond motion. The book will be a valuable resource for scholars interested in motion events, syntax-semantic interface, and typology"--